The Content of the Grounds and Conditions of Legitimate Harm Infliction During the Detention of the Offender under the Russian Criminal Legislation - V. V. Baburin; V. A. Ishmukhametova (Сибирское юридическое обозрение, 2012)
The article deals with the content of the grounds and conditions of legitimate harm infliction during the detention of the offender; the concept and features of legitimacy are revealed, the grounds and conditions of legitimate infliction of harm during the detention of the offender and examples of lawful and unlawful detention of the person who committed the crime are highlighted.